Extracellular differential proteome analysis of substrates of different lignin model compounds degraded by Aspergillus fumigatus G-13 - Li, Jinda; Du, Xia; Feng, Qian; Yan, Hong (Journal of Environmental Engineering and Landscape Management, 2020)
Aspergillus fumigatus G-13 has the potential to degrade lignocellulose biomass. The purpose of this work is to analyze the extracellular soluble secretory protein of lignocellulose degradation by Aspergillus fumigatus G-13. The research used ferulic acid, sinapic acid and p-coumaric acid as carbon sources. By controlling the culture conditions, adding cellulose co-substrate and auxiliary carbon source, the enzymatic production law of Aspergillus fumigatus G-13 degradation of three lignin model compounds was investigated. The two groups with the greatest difference in enzyme activity expression were screened, and high throughput quantitative proteomics analysis using iTRAQ. iTRAQ analysis showed that a total of 3862 protein spots changed significantly, of which 2103 down-regulated proteins and 1759 up-regulated proteins. The differential proteins involved in the degradation process of lignin model compounds are concentrated in dioxygenase, oxidoreductase, ferulic acid esterase B-2, isoamyl alcohol oxidase, bifunctional catalase peroxidase CAT2, cellulase, cytochrome P450 monooxygenase, flavin-binding monooxygenase, etc. Lignin-related differential abundance proteins were mapped to 128 metabolic pathways. Significantly enriched pathways include metabolic pathways, glyceride metabolism, oxidative phosphorylation, riboflavin metabolism, peroxisomes, riboflavin metabolism. The information presented in this paper is helpful to better understand the lignocellulose degradation mechanisms of A. fumigatus G-13.